Method validation of plasma or serum retinol analysis using high performane liquid chromatography UV/VIS detection - Trio, Phoebe Z.; Perlas, Leah A.; Ulanday, Joselita Rosario C. (2011)
Validation of analytical methods is essential in the generation of data for biochemical assessment studies to obtain reliable results that can be satisfactorily interpreted. For this purpose, the validation of plasma or serum retinol using high performance liquid chromatography was performed according to the requirements of ISO 17025 by taking into consideration the different criteria such as linearity, instrument detection limit, limit of quantitation and detection, trueness, repeatability, and reproducibility. The validation was carried out by using 100 uL of plasma or serum with 100 uL of retinyl acetate in absolute methanol. It was mixed for 2 seconds and extracted twice with 500 uL of hexane. The combined extracts were dried up under the stream of nitrogen gas. It was redissolved in 100 uL of 4:1 methanol-dichloromethane and 50 uL aliquot was injected to HPLC UV/VIS. Results showed that elution time of retinol was at 3.090±0.014 minutes and calibration standards behaved linearly (R^2=0.9994±0.0001) over the calibration range of 0.37-6.66 mg of retinol. The accuracy of the method evaluated from the analysis of the certified reference material was 102.89%. The %RSD of repeatability and reproducibility of the method were 3.35% and 3.76%, respectively. The detection limit was lower than the quantification limit and within the admitted performance range. The results of analysis performed to validate the analytical method for the determination of retinol in plasma or serum showed that they were within the performance criteria set for this method and they met the requirements of ISO 17025.
Keywords: High performance liquid chromatography